Detection of phytoplasmas causing grassy shoot disease in sugarcane by immunofluorescence technique - VISWANATHAN, R. (Indian Phytopathology, 2002)
This paper reports an indirect immunofluorescent technique developed for the detection of grassy shoot disease phytoplasmas in sugarcane. The systemic nature of the pathogen is confirmed.